Attitudes and beliefs of South African primary healthcare practitioners on initiating insulin in people with type 2 diabetes: Findings from the Tshwane Insulin Project (TIP). Issue 5 (October 2021) - Ngassa Piotie, Patrick; Wood, Paola; Muchiri, Jane W.; Webb, Elizabeth M.; Rheeder, Paul
Highlights: We used a cross-sectional survey to investigate the attitudes and beliefs of primary healthcare practitioners towards insulin therapy. The respondents included doctors as well as nurses. Doctors preferred to delay the initiation of insulin therapy, which is contrary to best practice guidelines. Patient behaviour namely reluctance to start insulin and non-adherence to treatment influenced doctors' prescription practices. Abstract: Aims: To investigate the attitudes and beliefs of primary healthcare practitioners (HCPs) towards initiating insulin therapy for people with type 2 diabetes (T2D) in South Africa. Methods: A cross-sectional survey was conducted amongst HCPs from 23 clinics. The nurses' questionnaire was administered by research nurses while doctors completed an online version about their attitudes, beliefs and perceived barriers to initiating insulin. Results: Of the 73 HCPs surveyed, 68% were nurses and 84% were women. Only 24% of HCPs believed that most patients would eventually need to initiate insulin regardless of their adherence to treatment regimens and 86% preferred to delay insulin therapy. Doctors were reluctant to initiate insulin, citing patient-related reasons such as low socio-economic level (41%), inability to refrigerate insulin (77%) and inability to self-monitor blood glucose (55%). Doctors mentioned that patient behaviour including not adhering to treatment regimen and appointments (91%) and reluctance to start insulin therapy (82%) influenced their prescription practices. Doctors mentioned that health system factors, including the pressure to see patients quickly (68%) and lack of continuity of care (64%) were barriers to initiating insulin. Conclusions: Optimising insulin therapy in primary care requires health system changes including promoting person-centred care and continuing training for HCPs.